ANALYSIS AND APPLICATION OF GENERALIZED DISTRIBUTION SECHk - A. V. Ausiannikau; V. M. Kozel (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The analysis of the robust properties of the generalized sechk-distribution is made. The possibility of producing natural-reduced maximum likelihood estimates of the offset parameter of the distribution is shown. Time-dependent density of the process described by the SDE with random structure centered at the transitions from one state to another is obtained. Examples of application of the generalized sechk distribution in statistical and technical problems are given.